Middle to Late Pleistocene dunefields in rocky coast settings at Cala Xuclar (Eivissa, Western Mediterranean): Recognition, architecture and luminescence chronology. (2nd July 2016) - del Valle, Laura; Gómez-Pujol, Lluís; Fornós, Joan J.; Timar-Gabor, Alida; Anechitei–Deacu, Valentina; Pomar, Francesc
Abstract: This study focuses on cliff-front anchored and sand-ramp aeolian dune accumulations in Cala Xuclar, Eivissa (Ibiza), Western Mediterranean, during different sea level falling stages from Middle to Late Pleistocene times. Stratigraphic mapping, conventional lithostratigraphic logging and OSL datings are used to reconstruct dune formation and evolution. Facies analyses result in the identification of six sedimentary units, three of which correspond to dune deposits formed at MIS 6 (145 ka), MIS 5d-c (∼100 ka) and MIS 4 (77–73 ka) respectively. Additionally there is a beach deposit at (∼2 m above present msl, which resembles the MIS 5a. This study concludes that each dune system corresponds to a relatively low sea-level stand that exposed enormous amounts of marine carbonate sands that was transported inland by migrating dunes under strong north–westerly winds. Therefore, sea-level fall and the related sediment supply owe likely to be key factors in the formation of these aeolianites systems.